2021
DOI: 10.1039/d1ce00590a
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of Ib diamond crystals synthesized in a Fe–Ni–C system with different SiC contents

Abstract: Silicon carbide (SiC) is a substance found in natural diamond inclusions. Analyzing the influence of SiC doping on the properties of synthetic diamonds is vital to understanding the growth mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The infrared absorption spectra of the crystals showed obvious infrared characteristic peaks of diamond at 1970, 2030, and 2160 cm –1 , which represent the vibrational energy level of the C–C bond, indicating that the synthesized crystals are diamond. According to the relevant literature, it becomes apparent that there is an obvious interaction between silicon and nitrogen during the diamond growth process. Doping with Si or SiC yields a reduction of the nitrogen content present within diamond. The removal of nitrogen impurities promotes the bonding of vacancies with silicon atoms in the crystal. In the experiments, Al was used as a nitrogen remover to promote the formation of SiV – color centers.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared absorption spectra of the crystals showed obvious infrared characteristic peaks of diamond at 1970, 2030, and 2160 cm –1 , which represent the vibrational energy level of the C–C bond, indicating that the synthesized crystals are diamond. According to the relevant literature, it becomes apparent that there is an obvious interaction between silicon and nitrogen during the diamond growth process. Doping with Si or SiC yields a reduction of the nitrogen content present within diamond. The removal of nitrogen impurities promotes the bonding of vacancies with silicon atoms in the crystal. In the experiments, Al was used as a nitrogen remover to promote the formation of SiV – color centers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, it is found that the luminescence intensity of the SiV – centers is too low, and the distribution of SiV – centers is not uniform. The reason is due to the abundant nitrogen doping reducing the luminescence intensity. …”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum of silicon-doped diamond single crystals is exceptionally clean, with only a strong and narrow peak observed near 1332.00 cm –1 , which is a typical diamond Raman characteristic peak. This observation confirms that all synthesized diamond single crystals in this experiment have a single sp 3 structure . In addition, the characteristic peak of graphite at 1580.00 cm –1 , which is common in many CVD diamonds, is absent in the diamond Raman spectra shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…This observation confirms that all synthesized diamond single crystals in this experiment have a single sp 3 structure. 38 In addition, the characteristic peak of graphite at 1580.00 cm −1 , 39 which is common in many CVD diamonds, is absent in the diamond Raman spectra shown in Figure 8. Therefore, there is no sp 2 graphite or sp 2 /sp 3 mixture in the silicon-doped diamond structures synthesized in this experiment, indicating that the chemical composition of the silicon-doped diamond samples synthesized by HPHT is highly pure.…”
Section: The Effect Of Si Content On Nitrogen Concentration In Diamondmentioning
confidence: 99%
“…For example, Denis Bogdanov et al 4 proposed that detonation nanodiamond cores grow in the form of graphite and diamond phases after annealing at a pressure of 5 GPa and a temperature of 1100–1500 °C; A. P. Yelisseyev et al 5 characterized a significant reduction in nitrogen in HPHT diamonds grown in Fe–C melts with low sulfur additions; Y. N. Palyanov et al 6 introduced the method of high-pressure synthesis of silicon diamond doped in Mg–Si–C system, and studied the influence of silicon on diamond crystal and spectral characteristics. For the optical centres in diamond, the effects of nitrogen concentration on the optical centres of Ib-type diamonds grown in FeNi alloys has been studied previously; 7 the successful entry of silicon into the diamond lattice as Si–C bonds in crystals synthesised with SiC as an additive in the FeNi–C system, laying the groundwork for further studies on the formation of Si–V colour centres; 8 and Miao et al have studied the PL spectra of B-rich diamonds grown in NiMnCo solvent before and after annealing and analysed the effect of boron doping and HPHT annealing on the optical centres of diamonds containing both Ni, Co, B and N impurities. 9 Many elements are involved in these systems, but for the pure Co–C system, only the effect of N in diamond on Co-related optical centres needs to be considered.…”
Section: Introductionmentioning
confidence: 99%